Geometric design practices for resurfacing, restoration, and rehabilitation - McGee, Hugh W. (Transportation Research Board, 2011)
"TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 417: Geometric Design Practices for Resurfacing, Restoration, and Rehabilitation documents the current state-of-the-practice related to nonfreeway resurfacing, restoration, and rehabilitation projects"--Publisher's description
Keywords: Pavements -- Maintenance and repair.; Pavements -- Design and construction.; Roads -- Maintenance and repair.; elektronické knihy; electronic books